DNA Damage Response Is Involved in the Developmental Toxicity of Mebendazole in Zebrafish Retina - Sasagawa, Shota; Nishimura, Yuhei; Kon, Tetsuo; Yamanaka, Yukiko; Murakami, Soichiro; Ashikawa, Yoshifumi; Yuge, Mizuki; Okabe, Shiko; Kawaguchi, Koki; Kawase, Reiko; Tanaka, Toshio (Frontiers in Pharmacology, 2016)
Intestinal helminths cause iron-deficiency anemia in pregnant women, associated with premature delivery, low birth weight, maternal ill health, and maternal death. Although benzimidazole compounds such as mebendazole (MBZ) are highly efficacious against helminths, there are limited data on its use during pregnancy. In this study, we performed in vivo imaging of the retinas of zebrafish larvae exposed to MBZ, and found that exposure to MBZ during 2 and 3 days post-fertilization caused malformation of the retinal layers. To identify the molecular mechanism underlying the developmental toxicity of MBZ, we performed transcriptome analysis of zebrafish eyes. The analysis revealed that the DNA damage response was involved in the developmental toxicity of MBZ. We were also able to demonstrate that inhibition of ATM significantly attenuated the apoptosis induced by MBZ in the zebrafish retina. These results suggest that MBZ causes developmental toxicity in the zebrafish retina at least partly by activating the DNA damage response, including ATM signaling, providing a potential adverse outcome pathway in the developmental toxicity of MBZ in mammals.